LITERASI REVIEW PERATURAN PEMERINTAH DAN LITERATUR AUDIT TERHADAP RPTs - Kusumaningdiah Retno Setiorini; Al Haq Kamal; Tyagita Dianingtyas Sudibyo (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2020)
This study is the result of a review of previous research in the Asian economy, which concerns the consequences and involvement of the problems that the company has in the case of the corporate scandal and the takeover of shareholder wealth (RPTs). RPTs have issues that will be discussed in this study, including the measures that will be used to implement the RPTs and variations in the size of the RPTs research. RPTs influenced by regulations, auditing and company management will be able to minimize the risk of the negative effects of these RPTs. Previous research has investigated the deterioration of shareholder wealth. The findings of previous studies related to RPTs in terms of shareholder wealth takeover, deterioration, undervaluation, reporting, increased risk of material misstatement and long-term deterioration of performance. Furthermore, the evidence suggests that regulations,corporate governance and auditing can reduce the negative effects of RPTs. These research engagements in providing information regarding the understanding for regulators on the effects of governance, corporate governance and external audits on reducing the negative effects of RPTs, and highlighting the increased risk of material misstatements in financial statement statements. The statute, in revealing how RPTs affect the risk assessment for auditors provides a starting point for future investigations of RPTs, not the least because it reveals important limitations with the extant body of research in this area. It also offers engagements and a depth of understanding that is striking to the eyes of policy makers and practitioners